2018
DOI: 10.3389/fncel.2018.00416
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Myosin Light Chain Kinase on the Occurrence and Development of Intracranial Aneurysm

Abstract: Myosin light chain kinase is a key enzyme in smooth muscle cell contraction. However, whether myosin light chain kinase plays a role in the occurrence or development of intracranial aneurysms is not clear. The present study explored the function of myosin light chain kinase in human intracranial aneurysm tissues. Five aneurysm samples and five control samples were collected, and smooth muscle cells (SMCs) were dissociated and cultured. A label-free proteomic analysis was performed to screen the differentially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
1
8
0
1
Order By: Relevance
“…Among these 180 proteins, 88 were significantly up‐regulated, and 92 were down‐regulated in the IA group compared to the STA group. The results were shown in our previous studies 16,17 …”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Among these 180 proteins, 88 were significantly up‐regulated, and 92 were down‐regulated in the IA group compared to the STA group. The results were shown in our previous studies 16,17 …”
Section: Resultssupporting
confidence: 82%
“…The absence of MYLK is known to be associated with several diseases, including aortic dissections 35 . We previously reported that SMCs extracted from human IA showed a trend of decreased MYLK expression and decreased contractile function 17 . SMCs depend on focal adhesion sites for their attachment to the ECM, which is crucial for effective contractions 36 .…”
Section: Discussionmentioning
confidence: 99%
“…MLCK is an important functional protein that regulates smooth muscle contraction. Activated MLCK phosphorylates the myosin light chain and phosphorylated myosin light chain induces smooth muscle contraction (8). MLCK was the first CaM-dependent kinase to be discovered and free Ca 2+ obtained after the binding of MLCK to calmodulin activates MLCK, which in turn activates contractile proteins (39).…”
Section: Discussionmentioning
confidence: 99%
“…Myosin light chain kinase (MLCK), a key molecule in the calcium signaling pathway (8), is expressed in hippocampal neurons, where it can accelerate the mobilization of synaptic vesicles, promote the release of various neurotransmitters and regulate the elongation of growth cones (9,10). A previous study found that the increase in nerve cell apoptosis observed in a rat model of ischemia-reperfusion brain injury might be associated with upregulation of MLCK expression and that the addition of a specific MLCK inhibitor (ML-7) significantly reduces neuronal apoptosis (11).…”
Section: Introductionmentioning
confidence: 99%
“…A parede do aneurisma pode demonstrar um gradiente espacial, com mudanças degenerativas importantes em direção ao domo do aneurisma. 42,44,45,49,50 Um estudo de 1999 comparou a parede arterial de aneurismas rotos e não rotos. 42 Os autores mostraram que aneurismas não rotos tendem a ter um endotélio intacto assim como as camadas da camada muscular lisa, com poucos macrófagos e outras células inflamatórias na parede arterial.…”
Section: Patologia Da Parede Arterialunclassified